Morphological classification of the tubercle of insertion of the transverse atlantal ligament: A computer tomography–based anatomical study of 200 subjects. Issue 6 (December 2019) - Mueller, Kyle; MacConnell, Ashley; Berkowitz, Frank; Voyadzis, Jean-Marc
Background and purpose: The atlantal tubercle is the attachment point of the transverse atlantal ligament, the main stabilizer of the atlantoaxial complex. No system of classification of the tubercle exists in the literature. We aimed to develop a morphologically based classification system of the atlantal tubercle to aid clinicians who deal with craniocervical pathology. Materials and methods: A retrospective review of computed tomography (CT) scans of the cervical spine was performed. The morphology of the atlantal tubercle was classified into four variants: rounded (classical), pointed, flattened, and hypoplastic. Age, presence, and morphological type were recorded. Results: A total of 200 CT scans were identified and reviewed. The tubercle was present bilaterally in all patients. Patients were equally distributed over various age ranges. The following morphological types were recorded: rounded (227/400; 56.8%), pointed (13/400; 3.3%), flattened (126; 31.5%), and hypoplastic (34/400; 8.5%). The same type was seen bilaterally in 68% (135/200) of patients. Morphological types appear equally on the right and left side of the atlas. Conclusions: The first morphologically based classification system of the atlantal tubercle utilizing CT is presented. Morphology type, especially hypoplastic type, may confer an increased risk for subsequent need for posterior fusion.